Fractal features of structures of gas flow in selected gas stations of I order - Gurgul, Henryk; Suder, Marcin (Managerial Economics, 2012)
This paper presents results of research focused on identification of nonlinear structures and deterministic chaos which take place in gas flows in provinces Małopolska and Podkarpackie. Taking into account time series of gas flows at stations Solec Zdrój, Czechówka, Miłocin, Głogów and Huta Sendzimira from time period between January 2007 and September 2011, the authors detected by mean of respective identifications methods the existence of nonlinear structures in these time series. However the results are not unique. Therefore, the preliminary results should be checked in further research on the basis of other stations located in other provinces of Poland and by mean of more advance methods. These future research should definitely confirm or reject the existence of chaotic structure of gas flows at the stations of first order.